First climatology of F-region UHF echoes observed by the AMISR-14 system at the Jicamarca radio observatory and comparison with the climatology of VHF echoes observed by the collocated JULIA radar - Massoud, Alexander A. (2024)
Coherent backscatter radar observations made at the Jicamarca Radio Observatory (JRO) have contributed significantly to our understanding of equatorial F-region irregularities. Radar observations, however, have been made predominantly at the Very-High Frequency (VHF) band (50 MHz), which corresponds to measurements of 3-m field-aligned irregularities. The deployment of the 14-panel version of the Advanced Modular Incoherent Scatter Radar (AMISR-14) at Jicamarca provided an opportunity for observations of Ultra-High Frequency (UHF - 445 MHz) echoes which correspond to measurements of irregularities with 0.34 m scale sizes. Here, we present what we believe to be the first report describing the quiet-time climatology of sub-meter equatorial F-region irregularities derived from UHF radar measurements. The measurements were made between August 2021 and February 2023 using a 10-beam AMISR-14 mode that scanned the F-region in the magnetic equatorial plane. The results show how F-region sub-meter irregularities respond to variations in season and solar flux conditions. The results also confirm, experimentally, that the occurrence of UHF F-region echoes is controlled by the occurrence of equatorial spread F (ESF). Higher occurrence rates were observed during pre-midnight hours and during Equinox and December solstice. Reduced occurrence rates were observed during June solstice. The results show that an increase in solar flux was followed by an increase in the altitude where noticeable occurrence rates start and in the maximum altitude of these occurrence rates. The observations also show that occurrence rates lasted longer (in local time) during low solar flux conditions. Comparisons with collocated VHF radar observations showed that, despite differences in radar parameters, observation days, and the scale size (one order of magnitude) of the scattering irregularities, the two systems show similar climatological variations with only minor differences in the absolute occurrence rates. Finally, the analysis of the occurrence rates for different beams did not show substantial climatological variations over local (within a few 100s of km) zonal distances around JRO. We point out, however, that observations on a single day can show strong local variations in echo detection and intensity within the AMISR-14 field of view due to the intrinsic development and decay of ESF structures.